2002
DOI: 10.1097/00001756-200212200-00029
|View full text |Cite
|
Sign up to set email alerts
|

Exercise increases mRNA levels for adhesion molecules N-CAM and L1 correlating with BDNF response

Abstract: In situ hybridization was used to evaluate whether long-term moderate locomotor exercise, which up-regulates BDNF and TrkB levels in the spinal gray matter of the adult rat, similarly influences the expression of the cell adhesion molecules N-CAM and L1. Exercise doubled the level of N-CAM mRNA hybridization signal in the lumbar spinal gray. The increase in L1 mRNA was less consistent. N-CAM mRNA levels slightly increased in the white matter. BDNF mRNA levels also increased in cells of the ventral horn and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 24 publications
0
23
2
Order By: Relevance
“…Loss of L1 immunoreactivity in chronic sedentary was not significantly different from that in chronic exercised animals (P Յ 0.18). and thus our results differ from those of Macias et al (2002). They recorded an increase in L1 mRNA in normal rats that were allowed 1 km of daily treadmill walking for 4 weeks but noted that the results did not reach statistical significance.…”
Section: E-h) and Ib4 (I-l) A-dcontrasting
confidence: 99%
See 2 more Smart Citations
“…Loss of L1 immunoreactivity in chronic sedentary was not significantly different from that in chronic exercised animals (P Յ 0.18). and thus our results differ from those of Macias et al (2002). They recorded an increase in L1 mRNA in normal rats that were allowed 1 km of daily treadmill walking for 4 weeks but noted that the results did not reach statistical significance.…”
Section: E-h) and Ib4 (I-l) A-dcontrasting
confidence: 99%
“…Exercise has been shown to increase neurogenesis in the mouse dentate gyrus (van Praag et al, 1999), to facilitate recovery from spinal cord injury (Barbeau et al, 1998;Edgerton et al, 2004), to increase growth factor expression (Gomez-Pinilla et al, 2002), and to regulate expression of cell adhesion molecules such as L1 (Itoh et al, 1997;Macias et al, 2002). However, the present study did not detect a change in L1 expression following exercise, …”
Section: Effect Of Exercise On L1 Expressioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Images were captured on a Leica DM5000B epifluorescence microscope using nonoverlapping ET series filters (Chroma Technology). For in situ hybridization to detect ALCAM or L1 mRNA, sense and antisense probes were generated from psBluescript SK plasmid containing mouse L1 cDNA (Macias et al, 2002) or a 900 bp fragment of mouse ALCAM cDNA (Weiner et al, 2004), and hybridization was performed using digoxigenin-labeled probes as described previously (Bartsch et al, 1994;Garrett and Weiner, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Macias et al [180] showed that rats exposed to long-term moderate locomotor exercise, in addition to showing enhanced levels of BDNF, also presented increased expression of both adhesion molecules, as evaluated in the spinal gray matter. Further studies are needed to establish if similar increases can also be found in specific brain regions.…”
Section: Clinical Evidencementioning
confidence: 99%